1997
DOI: 10.1177/107110079701801213
|View full text |Cite
|
Sign up to set email alerts
|

Acute Disruption of the Posterior Tibial Tendon Associated with Open-Fracture Dislocation of the Ankle

Abstract: A 27-year-old man with a high-energy, open-fracture dislocation of the ankle underwent debridement and open reduction of his injuries. During surgery a disruption-laceration of the posterior tibial tendon at the level of the fracture of the medial malleolus was found. Repair required location of the proximal muscle and tendon and controlled traction of the musculotendinous unit from its retracted position. Common aspects in the nine previously reported instances of this lesion include relatively high energy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 13 publications
0
13
0
1
Order By: Relevance
“…This type of injury is rare, with only 23 previously reported cases over the last 35 years. 1,[3][4][5][6][7][8][9][11][12][13][14][15][16][17][18] In concert with the current findings, the most common mechanism of injury includes forced pronation, external rotation, and dorsiflexion of the ankle, which places maximal stress on the tibialis posterior tendon. However, direct trauma to the tendon medially also may occur.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…This type of injury is rare, with only 23 previously reported cases over the last 35 years. 1,[3][4][5][6][7][8][9][11][12][13][14][15][16][17][18] In concert with the current findings, the most common mechanism of injury includes forced pronation, external rotation, and dorsiflexion of the ankle, which places maximal stress on the tibialis posterior tendon. However, direct trauma to the tendon medially also may occur.…”
Section: Discussionmentioning
confidence: 73%
“…2,17 Most cases involve a high-energy mechanism of injury, such as a motor vehicle collision or a fall from height. [1][2][3][4][5][6][7][8][9][10][13][14][15][16][17][18] However, lower-energy athletic injuries also have been described. 11,12 Rupture frequently occurs in a relatively hypovascular segment of the tendon, corresponding approximately to the level of the fracture site posteromedi-ally, which may indicate that the tendon lacerates against it.…”
Section: Discussionmentioning
confidence: 99%
“…La réduction et la stabilisation chirurgicale d'une fracture de la malléole médiale nécessitent la visualisation de la réduction non seulement en avant mais aussi en arrière pour ne pas méconnaître en peropératoire une lésion du tendon tibial postérieur et éliminer toute rotation du fragment. Une interposition inaperçue du tendon entre les fragments d'une fracture de la malléole médiale pourra conduire à une pseudarthrose lors d'un traitement orthopédique [ 8 ].…”
Section: Discussionunclassified
“…1,2 A current literature search revealed that these reported cases involved an open injury and/or a fracture of the medial malleolus. [1][2][3][4][5][6][7][8][9][10] As chronic PTT dysfunction can lead to progressive flatfoot deformity, ultimately leading to worsening pain and disability, 1,3,4 early recognition of acute PTT rupture associated with an ankle fracture is of utmost importance. Unfortunately, these injuries may easily go unnoticed secondary to pain limiting a thorough physical examination, [2][3][4][5] inability to identify the tendon rupture on standard plain ankle radiographs, 1 and difficulty identifying retracted ruptured segments intraoperatively.…”
Section: Levels Of Evidence: Descriptive Level V: Single Case Reportmentioning
confidence: 99%
“…1,2 A current literature search revealed that these reported cases involved an open injury and/or a fracture of the medial malleolus. 1-10…”
mentioning
confidence: 99%